Thin LGADs and thin silicon diodes for applications in radiotherapy - Milian, F. Mas; Data, E.; Vignati, A.; Donetti, M.; Centis Vignali, M.; Ferrero, M.; Ferrero, V.; Fiorina, E.; Monaco, V.; Montalvan Olivares, D.; Pennazio, F.; Pullia, M.; et al. (Frontiers in Sensors, 2025)
Low gain avalanche diodes (LGADs) and thin n-on-p silicon diodes, when read out by fast and custom electronics, exhibit characteristics that make them promising candidates for the development of new detectors for clinical applications such as beam commissioning, diagnostics and monitoring, dosimetry, and online treatment delivery verification. Compared to gas ionization chambers, these detectors offer significantly higher sensitivity, enabling the detection of single particles at fluxes of up to 108 particles/cm2s—sufficient to cover the entire clinical intensity range of carbon ion therapy and approximately one order of magnitude lower for proton therapy. Various front-end electronics have been developed and characterized for readout configurations, ranging from single channels (pads or strips) to arrays of up to 144 strips. These systems have been applied to single-particle identification for beam monitors in particle therapy, as well as to two-dimensional beam monitoring and dosimetry in ultra-high dose rate and spatially fractionated radiotherapy. This review summarizes the detectors based on LGADs and thin n-on-p silicon diodes developed within the INFN-CSN5 projects MoVeIT, SIG, and FRIDA. Specifically, we present a 2.7 × 2.7 cm2 particle counter for measuring beam fluence and position, a beam energy detector based on the primary particle’s time-of-flight, a setup for studying beam time structure at the nanosecond scale, and a system for range verification via prompt gamma timing. Current advances in various technologies are reviewed, together with challenges and future perspectives on the application of LGADs and thin silicon diodes in radiotherapy.